Leading an Internal Audit Function for The 21st Century – Experience of Telekom Malaysia - Mohammed, Hashim (Asian Journal of Accounting Perspectives, 2009)
Whilst the management philosophy and strategic thrusts in building an effective internal audit (IA) function are becoming clearer to most CAEs, the future must-win battle is really in Talent Management, as the competition from both outside and inside the company for key talent has intensified. The future sustainability of an IA function and value creation will depend on key individuals with mastery in not just accounting and internal auditing, but in general management skills, deep rooted business knowledge, leadership and the ability to create value. The traditional way of managing talent is not going to work in the future. How well managers and leaders understand the people’s personal aspirations and plans, and matching them with the company and function strategic needs will define the success of leading and transforming an IA function.